(untitled) (Revista Latino-Americana de Enfermagem, 2011)
Drugs consumption is as ancient as humanity. It has always existed and is associated with culture, in its historical and social context. The aim of this research is to know and analyze the perception of students from the Nursing School at the University of Guayaquil about legal and illegal drugs consumption. The methodological approach was qualitative, descriptive and exploratory. The sample consisted of eleven first-year students from the Nursing School. Individual and semi structured interviews were used for data collection. Thematic content analysis was adopted, in which five themes were identified: The economic situation, domestic violence, migration of close relatives, influence of the media that surround us, and ignorance about the topic. With a view to enhancing awareness on this hard reality that hurts and prejudices humanity, knowing students' perceptions contributes to identify their needs and create possibilities for health care interventions, particularly health promotion.